Soil Degradation Assessment in Major Land Use Systems in Sikar District of Western Rajasthan - Raina, Pramila; Kumar, Mahesh; Singh, Mohar; Chauhan, J S; Bohra, P C (Annals of Arid Zone, 2016)
Study on assessment of soil degradation in major land use system namely rainfed and irrigated crop lands, grazing lands and forest lands in Sikar District of western Rajasthan was conducted to identify the kind of soil degradation, its intensity and effect on soil fertility. Extensive and intensive field survey was carried out with the help of Survey of India toposheets, IRS-1A satellite imagery (Path 31 and Row 49) False Color Composite (band 2, 3, 4) on 1:50,000 scale. Wind erosion/sand deposition is the main soil degradation process identified in all the three land use systems. On satellite images, slightly degraded soil appears as pale brown with dark magenta tone indicating crop/vegetation cover (W1); moderately degraded soils in pale brown with patches of medium magenta tone (W2) light tone indicating sand piling and severe degraded soils in light yellow with whitish tones indicating extensive occurrence of typical dune features. The wind erosion degraded nearly 82.02% rainfed crop lands, 27.83% grazing lands, 40.69% irrigated crop lands and 8.44% forest lands. Water erosion is the main soil degradation process in forest and grazing lands that degraded about 76.98% and 38.17% area, respectively. Slight soil degradation appeared in uniform dark magenta tone in rainfed crop lands with uniform light pale brown to medium grey tone, medium degradation indicated by whitish grey patches of shallow soils with few stream channels and severe degradation is represented uniformly by light brown tone, intercepted by a number of streams that appear light gray in color. Combined degradation due to wind and water erosion accounted for 16.38% of grazing and 13.86% of forest lands. Salinity and alkalinity hazards degraded 17.58% area of grazing land. Surface soil samples from degraded and non-degraded sites of rainfed crop lands, irrigated crop lands and grazing lands were analyzed for soil fertility. The results revealed that organic carbon, available phosphorus and potassium were high in non-degraded sites than the degraded sites. Key words: Soil degradation, wind erosion, water erosion, satellite imagery